An investigation about the influence of migraine in students’ life quality of different years of medicine course from an institution of São José do Rio Preto (Research, Society and Development, 2020)
The migraine is a very common symptom in general population, expressing itself with a prevalence of more than 90% during lifetime, being characterized as a type of primary headache defined as a chronical neurovascular disturb, with clinical manifestation determined by interval headache crisis related to signs as photophobia, phonophobia, nausea, vomit, being also frequent the occurrence of neurological symptoms. The international headache classification presents categories of different headaches in types and subtypes, and the most common are the tensional headache and the migraine with or without aura. The university students constitute a risky population for migraine and tensional headache, and if these diseases are not treated, they can evolve to the chronical form, directly affecting the life quality of these individuals. The aim of this paper was to evaluate the influence of the headache in students’ life quality of different years of Medicine course and establish a relation between the undergraduation years and the pain worsening. The study was developed in a prospective descriptive way with 240 students. It was observed that the pains are more frequent throughout the course. However, great part of the interviewees did not consider that life quality was affected by affection, indicating a possible adaptation to the pain without affecting their daily activities. With the obtained data, it was necessary a bigger propagation about the crisis triggering factors, and the importance of the consultation to a neurologist for the correct diagnosis and treatment.